Neural tube defects in the Free State province from 2012 to 2016. Is there an increase? - Nické Theron; Gina Joubert; Bertram D. Henderson (AOSIS, 2020)
Background: Neural tube defects (NTDs) are anomalies of the central nervous system caused by the defective closure of the neural tube during early embryogenesis. A significant decline in the incidence of NTDs after folic acid fortification of food in South Africa was previously shown. Recently, clinical geneticists have voiced concerns that there is a possible resurgence in the number of NTDs. Objectives: The aim of this study was to determine the incidence of NTDs at a South African Hospital from 2012 to 2016. Methods: This is a retrospective cross-sectional study where all babies with NTDs born in, or referred to Universitas Hospital were included as study participants. Information was collected for both the mother and the baby from hospital records and data forms. Results: Seventy-seven cases of NTDs were captured from 2012 to 2016. The incidence of NTDs was 0.34/1000 births in the Free State province, and 1.21/1000 births if only the data for babies born in Universitas Hospital and Pelonomi Hospital were used. Further analysis showed a male: female ratio of 1:1. Open spina bifida was the most common defect at 71.4%. Conclusion: The incidence of NTDs in the Free State province was low compared to other South African and international studies. The incidence for the metropolitan hospitals is comparable to that of previous studies. This discrepancy is a marker of poor data recording and will impact healthcare planning. A statistically significant increase in NTDs could not be proven.